2018
DOI: 10.2147/ppa.s176262
|View full text |Cite
|
Sign up to set email alerts
|

Demand and willingness to pay for different treatment and care services among patients with heart diseases in Hanoi, Vietnam

Abstract: IntroductionIn Vietnam, cardiovascular diseases (CVDs) are serious health issues, especially in the context of overload central heart hospitals, insufficient primary healthcare, and lack of customer-oriented care and treatment. Attempts to measure demand and willingness-to-pay (WTP) for different CVD treatments and care services have been limited. This study explored the preferences and WTP of patients with heart diseases for different home- and hospital-based services in Hanoi, Vietnam.MethodsA cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…In this study, over 40% of patients were unemployed, and more than 90% did not have any other regular source of income hence could not readily commit themselves to paying for a service they may not be able to mobilize funds to support. These findings support previous work by Tran et al which reported that willingness to pay among relatively wealthy urban residents was higher compared to rural folks [ 22 ]. More so, a multi-center study conducted in developing countries showed a strong correlation between patients financial ability to pay for therapy and their willingness to pay [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, over 40% of patients were unemployed, and more than 90% did not have any other regular source of income hence could not readily commit themselves to paying for a service they may not be able to mobilize funds to support. These findings support previous work by Tran et al which reported that willingness to pay among relatively wealthy urban residents was higher compared to rural folks [ 22 ]. More so, a multi-center study conducted in developing countries showed a strong correlation between patients financial ability to pay for therapy and their willingness to pay [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the current study where the willingness to pay for kidney transplant service was low for majority of the patients. Another study by Tran et al (2018) in Vietnam showed similar findings of patients’ level of willingness to pay below the expected price of the services [ 22 ].…”
Section: Discussionmentioning
confidence: 70%
“…This study revealed that most ESKD patients were willing to pay for haemodialysis for themselves with a mean benefit of USD 25,999.06. Previous studies have reported contrasting findings on kidney replacement therapy in Ghana [ 18 ] and chronic illnesses in Malaysia and Vietnam [ 33 , 34 ]. In the current study, patients’ willingness to pay more for their use may be related to the rational expectations theory, which posits that individuals base their decisions on human rationality, information, and past experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Subjektivna procena daje dobar uvid u dugotrajne efekte plaćanja zdravstvene zaštite i finansijsku opterećenost domaćinstva (15), a kao rezultat subjektivne procene velikog finansijskog opterećenja usled plaćanja zdravstvene zaštite ispitanici izbegavaju korišćenje zdravstvenih usluga ili bi platili manje od njihove aktuelne cene (1,16).…”
Section: Merenje Finansijskog Opterećenja Usled Korišćenja Zdravstven...unclassified